The acute impact of the intake of four types of bread on satiety and blood concentrations of glucose, insulin, free fatty acids, triglyceride and acylated ghrelin. A randomized controlled cross-over trial. (February 2017) - Bo, S; Seletto, M; Choc, A; Ponzo, V; Lezo, A; Demagistris, A; Evangelista, A; Ciccone, G; Bertolino, M; Cassader, M; Gambino, R
Abstract: The purpose of the present study is to compare the effects of four different breads (one commercial par-baked wheat bread, three sourdough breads prepared with commercial wheat flour, organic wheat flour, organic einkorn flour) in 16 healthy subjects. The primary outcome of this randomized cross-over trial was evaluating intra-individual changes in glycemic areas-under-the-curve (AUCs) after 50 g carbohydrate portions of each bread; secondary outcomes were changes in insulin, fatty free acids (FFA), triglyceride, acylated ghrelin and satiety AUCs. Blood samples and satiety ratings were collected every 30-min for 2-h after the consumption of each bread. The einkorn flour showed the lowest amylase activity, the commercial flour the highest; commercial bread had the highest carbohydrate content and the lowest dietary fiber content. Glucose AUCs were significantly lower after the consumption of sourdough breads made with organic (12, 754 ± 1433 mg/dL × h) and einkorn flour (12, 216 ± 1210 mg/dL × h), with respect to the commercial bread (13, 849 ± 2193 mg/dL × h). Insulin AUCs decreased after the consumption of all sourdough breads when compared to commercial bread. FFA and triglyceride AUCs did not differ by kind of breads. Median ghrelin AUC was significantly lower and satiety higher after the einkorn bread (3710 pg/mL × h; 3225 ± 2414, respectively) than after commercial bread consumption (4140 pg/mL × h; 1706 ± 1766, respectively), but not with other sourdough breads. In conclusion, the use of sourdough may improve the nutritional features of breads; einkorn bread induced the least disturbance in carbohydrate homeostasis and the greater satiety. If confirmed by further research, these results might have implications in the approach towards chronic dysmetabolic diseases. Graphical abstract: Intra-individual changes in glycemic, insulinemic, free fatty acids, triglyceride, acylated ghrelin and satiety areas-under-the-curve after the consumption of a 50 g carbohydrate portion of four breads were evaluated in sixteen healthy subjects. The order of consumption of the four breads (commercial bread, sourdough bread with commercial wheat flour, sourdough bread with organic wheat flour, sourdough bread with einkorn organic flour) was randomized (R) for each participant. Highlights: Glucose areas under the curve (AUCs) were lower with sourdough breads. Insulin AUCs decreased after the consumption of all sourdough breads. Satiety was higher after einkorn bread, but not with the other sourdough breads.